Objectiving of humanistic ideas in the culture of Ukraine in XVII century - T. K. Ognieva (Ukrainian Cultural Studies, 2018)
The article is devoted to the analysis of culturological processes in the period of formation of the first national revival of Ukraine in the XVII century. Unlike previous historical periods, a human being and nature become the object of artistic and aesthetic research; the desire for artistic transformation of the real world becomes the stimulus of literature and art development. The need for knowledge, the development of positions, forms and methods of liberation of human mind from a dogmatic-religious outlook is manifested in the secularization of Ukrainian culture in the seventeenth century. West European Renaissance made a significant impact on the change of world-view conception in Ukrainian culture. On the territory of Ukraine various, sometimes opposing, influences were mixed – those from Byzantium and Western European countries; therefore, national culture was formed at the crossroads of Eastern and European cultures. We can trace two main directions in which Ukrainian Renaissance was moving: firstly, transformation of Greek-Byzantine Slavic spiritual traditions in the circumstances of Catholic counterreformation and the formation of the church union, and the second – the perception and transformation of European humanism in the Renaissance period. The period that came after the Middle Ages comprehensively disclosed a human being both in social and aesthetical artistic aspect, and the movement of humanistic ideas in Western and Eastern Europe has led to a deeper interest in human personality. Ukraine did not erode this process, and gradually formed a new human ideal, based on individual culture, spiritual freedom, and redefined the purpose of man in the world. The complex political and socioeconomic conditions of the seventeenth century in Ukraine required special, progressive at that time, characteristics of the development of culturological tendencies. The broad cultural national movement, whose roots were in the resistance to Polish – gentry oppression and the struggle against the Catholic church, brought about flourishing of book printing, the spread of education and scientific knowledge and the rise of anthropocentric worldview in art and literature. An important aspect of Renaissance thinking is the desire to thoroughly explore the real surrounding world, which brings the path to science and education. It is these discoveries of the Ukrainian Renaissance worldview that are gaining momentum in the spiritual culture of Ukraine in the seventeenth century.